Effect of Temperature on Growth, Hemagglutination, and Protease Activity of Porphyromonas gingivalis - Percival, Rimondia S. (American Society for Microbiology, 1999)
Bacteria persisting in periodontal pockets are exposed to elevated temperatures during periods of inflammation. Temperature is an environmental factor that can modulate gene expression. Consequently, in the present study we examined the effect of temperature on the expression of virulence determinants by the periodontopathogen, Porphyromonas gingivalis. P. gingivalis W50 was grown in a complex medium under hemin excess at pH 7.0 and at a constant temperature of either 37, 39, or 41°C; cultures were monitored for protease and hemagglutinin activity. P. gingivalis grew well at all three temperatures. An increase in growth temperature from 37 to 39°C resulted in a 65% reduction in both total arginine- and lysine-specific activities (P < 0.01). A further rise in growth temperature to 41°C led to even greater reductions in arginine-specific (82%; P < 0.001) and lysine-specific (73%; P < 0.01) activities. These reductions were also associated with an altered distribution of individual arginine-specific enzyme isoforms. At 41°C, there was a disproportionate reduction in the level of the heterodimeric RI protease, which also contains adhesin domains. The reduction also correlated with a markedly diminished hemagglutination activity of cells, especially in those grown at 41°C, and a reduced immunoreactivity with a monoclonal antibody which recognizes gene products involved in hemagglutination. Thus, as the environmental temperature increased, P. gingivalis adopted a less aggressive phenotype, while retaining cell population levels. The coordinate down-regulation of virulence gene expression in response to an environmental cue linked to the intensity of the host inflammatory response is consistent with the clinically observed cyclical nature of disease progression in periodontal diseases.